Application of a comprehensive rock slope stability assessment approach for selected Malaysian granitic rock slopes - Afiq Farhan Abdul Rahim,; Abdul Ghani Md Rafek,; Ailie Sofyiana Serasa,; Rini Asnida Abdullah,; Afikah Rahim,; Wan Salmi Wan Harun,; Foong, Swee Yeok; Abdurrahman, Muslim; Lee, Khai Ern; Huy, Nguyen Xuan; Xuan, Tran Van; Goh, Thian Lai (Penerbit Universiti Kebangsaan Malaysia, 2022)
In Malaysia, rock slope stability analysis has been largely confined to kinematic analysis with rock mass rating systems as assessment tools for stability analysis. While this method addresses the fundamental issues of rock slope stability including identifying potential failure modes, an information gap still exists between geologists and engineers in designing proper mitigation measures for rock slopes. This paper aims to address this issue by incorporating several methodologies, including kinematic analysis, slope mass rating and the Barton-Bandis criterion for the limit equilibrium method. Four rock slopes with potential instabilities namely KSA, KSB, LHA, and LHB were studied. KSA and KSB were located near Kajang, Selangor while LHA and LHB were located near Rawang, Selangor. Each slope exhibits multiple potential failures, with attention given on sliding-type failures in planar or wedge form. A slope mass rating value was assigned to each potential failure based on rock mass ratingbasic and the slope mass rating based on readjustments for discontinuity orientation and excavation method. Factor of safety from limit equilibrium method show potentially unstable blocks and failed blocks (Factor of Safety <1.00) with confirmation on site. Water filling of discontinuity apertures plays an important role in destabilizing rock blocks, especially in wet conditions experienced in Malaysia’s tropical climate. Several geometries are identified as potentially unstable due to low slope mass rating (Class V) and factor of safety of <1.2, such as planar J5 and wedge J2*J5 at KSA, wedge forming with sets J3, J4 and fault plane at KSB, planar J2 at LHA, and wedge J3*J4 at LHB. Stabilization structures such as rock bolts can be better designed with the determined factor of safety values coupled with relevant geological and geotechnical inputs. In this comprehensive rock slope stability assessment approach, limit equilibrium method serves as a useful method in analyzing rock slope stability to complement kinematic analysis and stability ratings often used in Malaysia.